Factors Influencing Dietary Diversity and Nutritional Status Among Adolescent Pregnant Women in South-Eastern Tanzania: A Hospital-Based Cross-Sectional Study - Miriam P. Muga; Godfrey C. Katusi (International Journal of Nutrition, 2024)
Introduction Adolescent pregnancy has become a global health concern in recent years, with maintaining dietary diversity being essential to ensure the health of both the mother and fetus. This study aimed to understand the dietary diversity and nutritional status among pregnant adolescents attending antenatal clinic and identify the factors influencing these outcomes. Methodology A hospital based cross-sectional study was done at St Francis Regional Referral Hospital at Ifakara, Tanzania. A total of 131 adolescent pregnant women consented to participate. Data was obtained using questionnaire and 24-hour dietary recall. Results The study revealed that 93.1% (n=122) of adolescent pregnant women met the minimum dietary diversity score based on 24-hour recall period. Similar proportions were observed for age group but vary significantly with the number of children born (p< 0.001), marital status (p = 0.032) and education level (p< 0.001). Additionally, 93.9% (n=123) of adolescent pregnant women had a normal Mid-Upper Arm Circumference (MUAC) and 6.1% (n=8) were undernourished. Similar proportions were observed across age, number of children born, marital status, education status, and occupation. Conclusion Most adolescent pregnant women in this study achieved adequate dietary diversity. However, socio-demographic factors such as age, marital status, and education, as well as challenges like illness and loss of appetite, influenced their dietary diversity and overall nutritional status. Future research should adopt a community-based longitudinal approach to better understand these factors and provide a more comprehensive understanding on the dietary patterns of adolescent pregnant women.
Keywords: Dietary diversity